Anxiety and adaptation to pandemic in Mexico: A cross-sectional study - Álvarez Bermúdez, Javier (2022)
Background: An aspect that becomes relevant in the current pandemic situation is the probable psychological effects that it may cause. A series of studies have shown that these kinds of critical situations have effects such as the development of anxiety processes in people. Hence the interest in knowing how health habits help to adapt to the pandemic and mediate anxiety processes. Objective: to analyze the relationship of healthy habits with anxiety and adaptation to confinement. Method: 7,439 people from Mexico participated, with ages between 18 and 80 years (M = 36.99, SD = 14.00). Results: We found that sleep (58%), eating (29%) and physical activity (52%) habits have been affected by confinement; 11.5% of the participants showed indicators of anxiety. The 9% of participants adapted poorly to confinement. The variable that best predicts adaptation to confinement is anxiety, followed by food, sleep, and physical activity. Those who are most affected by habits are young people and women by gender. Conclusions: The pandemic has led to changes in negative habits in a large sector of the population, which are now considered risk factors for physical and mental health. In addition, habits are associated with anxiety and adaptation, so it is necessary to provide society with strategies that allow proper management of habits, which can prevent the manifestation of anxiety.